Tissue Engineering From Lab to Clinic - Pallua, Norbert; Suscheck, Christoph V.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Tissue engineering is a multidisciplinary field incorporating the principles of biology, chemistry, engineering, and medicine to create biological substitutes of native tissues for scientific research or clinical use. Applications of this technology include studies of tissue development and function, investigations of drug response, and tissue repair and replacement. Tissue engineering is rapidly becoming one of the most promising treatment options for patients suffering from tissue failure. This abundantly illustrated and clearly structured guide, written by leading experts, is intended to serve as a reference for all clinicians and researchers who deal with tissue engineering issues in their daily practice and for students studying tissue engineering at both the undergraduate and the graduate level. It will also be invaluable for professionals in related research areas, particularly those where cell and tissue culture is a new or emerging tool. The book is divided into three sections that present the latest findings in tissue engineering and their application in clinical practice. The first section discusses the basics and principles of tissue engineering, including scaffolds, cells, and technologies. The second and third sections then address in detail the tissue engineering of specific organs and tissue types. A visual approach is emphasized throughout, with numerous self-explanatory graphics, diagrams, and photos.
BASICS AND PRINCIPLES: Scaffolds: Micro and Nano Technology -- Biomimetic Materials -- Natural and Synthetic Scaffolds: Adhesion, ECM, Structure, Function, Modification -- Cells: Sources, Growth, Differentiation, Trans-Differentiation -- Embryonic Stem Cells: Sources and Characterization -- Adult Stem Cells: Sources and Characterization -- Isolation and Growth -- Differentiation and Plasticity -- Regulation Mechanisms: Key Signaling Molecules -- Cell and Organ preservation -- Engineering Technologies: Animal Models for Evaluation of Tissue Engineering Constructs -- Biomedical Imaging and Image Processing -- Bioreactors for Tissue Engineering -- Drug delivery -- Gene Therapy -- OROGANS: Liver -- Musculoskeletal Tissues -- Lung -- CNS -- Peripheral Nervous System -- Nephrons -- Biohybrid organs -- Heart and Cardiovascular Engineering -- Eye/Retina -- Respiratory Systems Engineering -- Ear -- Skin -- TISSUE TYPES: Adipose Tissue -- Blood Substitutes -- Angiogenesis and Vascularization -- Bone Tissue -- Brain Tissues -- Cartilage Tissue -- Pancreatic Tissues -- Tendons -- Tissue Engineering in Reproductive Medicine, of Heart Valves, in Oral and Maxillofacial Surgery -- Uro-Gital System/Bladder Tissue.
Keywords: Medicine; Human genetics; Medical laboratories; Biochemistry; Surgery; Microbiology; Biomaterials; Biomedicine; Human Genetics; Plastic Surgery; Medical Biochemistry; Laboratory Medicine; Biomaterials; Microbiology